A plea for appraisal and appreciation of immunohistochemistry in the assessment of prognostic and predictive markers in invasive breast cancer. (February 2018) - Van Bockstal, Mieke; Floris, Giuseppe; Galant, Christine; Lambein, Kathleen; Libbrecht, Louis
Abstract: This viewpoint is a personal reflection on the values and merits of immunohistochemistry in current breast cancer diagnosis. Immunohistochemistry is a validated mainstay in molecular subtyping of invasive breast cancer. Immunohistochemical assessment of hormone receptor status and HER2 expression is used to determine the clinico-pathological surrogate of breast cancer intrinsic subtypes, which guide neoadjuvant and adjuvant therapy. The advent of genomic prognostic signatures and qualitative mRNA-based assays makes some clinicians and researchers wonder whether immunohistochemistry should be abandoned. However, the perils and pitfalls of these mRNA-based tests cannot be neglected. This viewpoint offers a brief overview of quality issues in immunohistochemistry and qPCR, as well as a concise summary of currently available evidence on the correlation of immunohistochemistry and mRNA-based testing for prognostic and predictive markers in invasive breast cancer. We strongly advocate the use of immunohistochemistry as it integrates valuable spatial information with quantification of protein expression.